Effects of Extra Curricular and Co-curricular Activities to the Academic Performance of Intermediate Pupils - Ma Romica Gelline T De Vera; Phillip G Queroda (ASEAN Multidisciplinary Research Journal, 2020)
This study was made to determine the effects of extra and co-curricular activities to the academic performance of intermediate pupils in Binmaley I District, Binmaley, Pangasinan. Public schools in the elementary level in Binmaley District 1 are mostly with big campuses with standard number of pupils and sample teaching force. Majority of the schools holds 5-7 co-curricular activities. More so, the majority of the learners participate in the co-curricular activities in school, district, division and regional levels. The participation of the learners to the co-curricular activities contributes to attaining their learning competencies. The school profile has not related to the extent of contribution of the majority of the co-curricular activities to pupils’ learning competencies. Among the top problems encountered by the learners in participating Co-Curricular activities dwell on the pupils’ struggle with time management, short attention span, costly activities, the difficulty of coping up and tardiness. Based on the findings and conclusions, it is recommended that public elementary schools should sustain the conduct of co-curricular activities and explore more innovative and interactive activities to reach out to more learners. They should also promote and give more emphasis on the participation of co-curricular activities. Further, since profile variables do not affect the extent of contribution of the majority of the co-curricular activities to pupils’ learning competencies, it should be part of the curriculum for good.